Unfinished business: integrating individual decision-makers' experience and incentives to organizational performance feedback theory - Blettner, Daniela; Kotiloglu, Serhan; Lechler, Thomas G. (Frontiers in Psychology, 2023)
In this paper, we analyze the role of individual decision-makers in organizational decision-making that is described by the Carnegie perspective. In particular, building on the Behavioral Theory of the Firm, we analyze the influence of decision makers on organizational responses to performance feedback. Managers in organizations can influence the performance feedback process through their individual experience. Moreover, they are motivated and controlled by incentives, which is another mechanism by which organizational decision making can be influenced by individuals. While the Carnegie perspective acknowledges that decision-makers interpret performance feedback and initiate organizational responses, individuals are not as closely integrated to the organizational performance feedback process as some othermostly organizationalconditions. Recently, several intriguing empirical studies have addressed the role of experience and incentives in the performance feedback process. However, their cumulative effect remained impossible to assess. We meta-analytically review 205 BTOF studies to test our hypotheses on the influence of decision-makers' experience and incentives on organizational responses to performance feedback. We show that decision-makers' job experience and domain expertise influence organizational responses to performance below aspirations, while incentives and compensation become relevant when performance is above aspirations. These results highlight the importance of individual decision-makers in explaining variations in organizational performance feedback decisions, offering exciting venues for psychology scholars to contribute to the Carnegie perspective.